The BSNL Saga: Individual Volition vs. Systemic Coercion in Voluntary Retirement Schemes - Swapan Deep Arora; Ananya Syal (Vikalpa)
Abhishek has spent most of his life working for a public enterprise, Bharat Sanchar Nigam Limited (BSNL), engaged in providing telecom services. As he nears his silver jubilee with BSNL, a hard decision of whether to opt for Voluntary Retirement Scheme (VRS) is thrust on him. Looking back at his career, Abhishek has several positive takeaways and believes he has more than a decade to offer his beloved organisation. However, Abhishek is also cognizant of many factors that structurally push him toward the singular alternative of separation, and the degree of volition in his decision appears strangulated.